Sports injury surveillance in Japan (from Sports Safety Association) - Fukubayashi, T.; Ogawa, T.; Fukano, M. (Sports injuries and prevention, 2015)
The chapters of this book focus on the development of a better understanding of the mechanisms and risk factors involved in sports-related injuries. Implicit in this understanding is the attempt, also covered in this book, to create intervention programs which minimize or prevent sports related injuries In this initial chapter we provide a foundation for the ensuing chapters by assessing the current incidence and general features of sports-related injuries in Japan. We herein supply the latest statistics on the incidence of sports-related injuries in Japan on the basis of surveillance conducted by the Sports Safety Association in the fiscal years from 2000 to 2011. We hope our organization of the statistical material, and our structured arrangement by anatomical site, type and severity of disorder, type of sport, and gender will allow readers to easily access needed information as well as better understand the contents in the later chapters of this book.